2020
DOI: 10.3389/fvets.2020.569167
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Four Dairy Farming Scenarios in an Alpine Environment: The Case Study of Toma di Lanzo Cheese

Abstract: The dairy sector accounts for a large share of all European agricultural production, at the same time however, it is one of the most ascribed sector contributors to the environmental impact of agriculture, particularly for greenhouse gas emissions. Simultaneously, it is a strategic sector for the economy but generates increasing debate in the community regarding the social aspects mainly related to the use of resources and the food-feed competition of livestock involving the reduction of human-edible crops. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…The facilities were also cleaned with tap water only. Results reported values comparable with the WD estimated by other researchers [34,67], equal to 0.52 m 3 and 0.3 m 3 , respectively. Zucali et al [68], focusing on 17 dairy goat farms, also found similar results (0.39 ± 0.15 m 3 ) without specifying the distinguished contributors.…”
Section: Results Without Allocationsupporting
confidence: 89%
See 1 more Smart Citation
“…The facilities were also cleaned with tap water only. Results reported values comparable with the WD estimated by other researchers [34,67], equal to 0.52 m 3 and 0.3 m 3 , respectively. Zucali et al [68], focusing on 17 dairy goat farms, also found similar results (0.39 ± 0.15 m 3 ) without specifying the distinguished contributors.…”
Section: Results Without Allocationsupporting
confidence: 89%
“…Roer et al [63], adopting as the FU 1 kg ECM, reported values ranging from 89.3 to 111 g oil -eq in the Norwegian farms previously described. Differently, Noya et al (2018) and Verduna et al (2020) [34,67] choosing as the FU 1 kg FPCM, showed low impacts for FD (41.5 and 55 g oil -eq , respectively). Knudsen et al [50] estimated as impact category mineral, fossil and renewable resource depletion (mg Sb/kg FPCM) and showed that the organic production of milk from the grassland-based and mountainous systems contributed much less to this impact category than the organic milk from the mixed system.…”
Section: Results Without Allocationmentioning
confidence: 86%
“…However, in a countertrend, “green” consumption orientations are emerging, characterized by food choices of products, including milk, which are linked to tradition and are local and sustainable [ 23 ]. The dairy sector in Italy is extremely heterogeneous in terms of territorial distribution, companies’ size, and herd management, with a good proportion of small family-run businesses based on traditional production systems [ 24 ] that are more sustainable for the environment and the territory in which they are located [ 25 ]. It is therefore important to properly communicate the value (e.g., local branding) and the higher quality of the products obtained from these local systems as differentiation tools on the market to increase transparency and create greater consumer awareness [ 1 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although one of the suggested strategies was to reduce the inputs, other views suggest enhancing the waste outputs, too. Another strand, in fact, concerns studies that have designed the possibility of transitioning to a more sustainable system through a circular economy approach [24,25], which is intended to be a system-wide approach to economic development that is designed for the benefit of businesses, society, and the environment [26]. The transition to a circular economy can result in a minimization of the use of external inputs and in the reduction of waste and emissions into the environment through the recycling and valorization of agricultural waste [27], thus avoiding the exploitation animals but using them "for what they know how to do" [28].…”
Section: Introductionmentioning
confidence: 99%